Pengaruh Hari Perdagangan Saham Terhadap Return Saham Harian di Bursa Efek Jakarta - Ida Nur Hayati (Dinamik, 2002)
Study for the effect of share trading days to the daily share returns in Stock Exchange has been carried out most invarious countries. Overseas studies produce consistent findings that the daily share returns results in negative impact on Monday (Monday Effect) and resulting inpositive impact on Friday (Week End Effect). Those effects are called as day of the week effect. The similar studies carried out Indonesia have not obtained consistent findings as similar as overseas including overseas studies make use of Ordinary Least Squares (OLS). Whereas this study does not utilize this approach, as most of the assumptions could not be fulfilled. Technical Approaches dealt with the share returns calculation dominantly affect to the amount of daily share return. These are due to the facts that the irrational factors also used by the investors to do the transactions. Consequently, the demand and supply of the share are also influenced by the behaviour of the investors them elves. Statistical approach used for examining the day effects is Autoregressive Moving Average (ARIMA) Approach. This approach is chosen as there is no hetero scedasticity or there is an existence of stationary data. To examine the difference of share trading day effects to the share returns this study utilizes Analysis of Variance (ANOVA), 244 daily aggregate share price indexes (IHSG) and LQ45 Indexes are used for this study. The findings of this study suggest that (1) all of the share trading days give a positive impact on the share returns, (2) daily aggregate share price indexes (IHSG) do significantly affect the share returns on Thursday and (3) LQ45 Indexes do significantly affect the share returns on Thursday and Friday. These findings imply that the investors should consider the day effects in deciding to be involved in share trading so that they could maximize their future returns.